PENGARUH KUALITAS PELAYANAN DAN PERSEPSI HARGA TERHADAP KEPUASAN PELANGGAN MNC PLAY (STUDI KASUS MASYARAKAT KELURAHAN TANJUNG REJO) - Sembiring , Dea Ranika; Sabrina , Hesti; Pribadi , Teddi (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
This research aims to determine "The influence of service quality and price perception on Mnc play customer satisfaction (case study of the Tanjung Rejo Village Community). This research uses quantitative research methods with the aim of analyzing the influence between two or more variables. The sample in this study was the Tangjung Rejo Village Community who used Mnc play. In this research, researchers carried out questionnaires. Test the data in this study using SPSS 25. Based on the results of the partial test (t), service quality and price perception have a positive and significant effect on customer satisfaction. In the Determination Coefficient Test (R2), the Adjusted R Square value was 54.8%, while the remaining 45.2% was influenced by other factors not included in this research.